Project Manager 2007 (Master of Softwware Engineering) - Tuzmen, Metin (University of Wisconsin -- La Crosse, 2007)
Every software employs certain level of project management system. Irrespective of the size of the team that builds the software, good project management skills and tools will always make developing the software easier, maintainable and within the proposed budget. However, when project management fails to perform the right tasks, the software development process results increasing costs, and serious problems, and fails in its promised value. This could even lead to the project being abandoned and resources being demoralized. Many tools have been developed to streamline project management. Some of them help project managers control project schedule, others do budget controls, and yet others allow addition of other components such as requirements management and/or code management. Project Management 2007 is a project which realizes the importance of project management, not just as a place to control a certain project, but as a place where software engineering activities can be managed and learned for better performance and refining these activities to fit the real world. Project Manager 2007 manages projects at an organizational level, where each project is defined in qualitative details based on the organization's structure and software engineering techniques. Project managers as well as other mid-high level managers can learn about their organization, software development capacities and can give direction to new initiatives to improve quality of the software. Project Manager 2007 addresses project management, organization management, resource management, risk management, skill management, document management, metrics management and requirements management.
Keywords: Computer software -- Development -- Management.